2022
DOI: 10.3390/biomedicines10051073
|View full text |Cite|
|
Sign up to set email alerts
|

Toxic Exposure to Endocrine Disruptors Worsens Parkinson’s Disease Progression through NRF2/HO-1 Alteration

Abstract: Human exposure to endocrine disruptors (EDs) has attracted considerable attention in recent years. Different studies showed that ED exposure may exacerbate the deterioration of the nervous system’s dopaminergic capacity and cerebral inflammation, suggesting a promotion of neurodegeneration. In that regard, the aim of this research was to investigate the impact of ED exposure on the neuroinflammation and oxidative stress in an experimental model of Parkinson's disease (PD). PD was induced by intraperitoneally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Additionally, vinclozolin prepubertal exposure in male rats inhibits pubertal maturation and slows the growth of the accessory sex gland and epididymis [ 36 ]. D’Amico and colleagues recently demonstrated that the effect of endocrine disruptor exposure was not limited to the urogenital apparatus [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, vinclozolin prepubertal exposure in male rats inhibits pubertal maturation and slows the growth of the accessory sex gland and epididymis [ 36 ]. D’Amico and colleagues recently demonstrated that the effect of endocrine disruptor exposure was not limited to the urogenital apparatus [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dose and route of administration were based on previous studies [ 23 , 37 ] and according to a preliminary experiment ( Figure S1 ). Vinclozolin was administered at three doses (30, 100, and 300 mg/kg) for 7 and 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Extracts from cytosol and nucleus were prepared as previously described and incubated with the antibodies anti-NRF-2 (1–500, SCB, Heidelberg, Germany, #sc-365949), anti-heme oxygenase 1 (HO-1; 1-500, SCB, Heidelberg, Germany, #sc-136960), anti-β-tubulin (1–500, SCB, Heidelberg, Germany, #sc-166729), and anti-MAP2 (1–500, SCB, Heidelberg, Germany, #sc-74421) in 1× PBS, 5% w / v non-fat dried milk and 0.1% Tween-20 at 4 °C overnight [ 46 , 47 , 48 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. For the cytosolic and nuclear fraction, blots were also probed with β-actin and lamin A/C protein to ensure that they were filled with equivalent amounts of proteins (1:500; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they demonstrated an alteration in antioxidant endogenous defense, reflected in an increase in Mn-SOD activity after vinclozolin exposure [ 8 ]. Following this study, D’Amico et al demonstrated that exposure to vinclozolin (and other endocrine disruptors) significantly induced oxidative stress and inflammation, worsening arthritis and Parkinson’s disease in experimental murine models [ 9 , 10 ]. In consideration of the fact that most previous studies investigated the effects of vinclozolin exposure on the reproductive system, we investigated for the first time the impact of long exposure to vinclozolin on the respiratory system [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 95%